Recanalisation and ulcer recurrence rates following ultrasound-guided foam sclerotherapy. (August 2016) - Howard, Julia K; Slim, Fiona JA; Wakely, Margaret C; Emerson, Lorraine G; Davies, Colin E; Kulkarni, Sachin R; Bulbulia, Richard A; Whyman, Mark R; Poskitt, Keith R
Objectives: The aim was to assess vein recanalisation and ulcer recurrence in patients with chronic venous ulceration following ultrasound-guided foam sclerotherapy. Method: Open (CEAP 6) or recently healed (CEAP 5) chronic venous leg ulcers were treated with foam sclerotherapy between July 2010 and August 2012. Venous duplex scans were performed two weeks and one and two years post treatment, recording recanalisation and reflux. One- and two-year ulcer recurrence rates were calculated using Kaplan–Meier survival analysis. Results: A total of 100 legs were treated in 92 patients; 86 were CEAP 5 and 14 were CEAP 6. At two weeks complete or short segment occlusion was demonstrated in 99/100 legs. Complete follow-up was 93% at one year and 88% at two years. Complete and segmental recanalisation with new reflux was recorded in 11/93 (12%) legs and 25/93 (27%) legs, respectively (overall 36/93; 39%) at one year; and 6/88 (7%) legs and 15/88 (17%) legs, respectively (overall 21/88; 24%) at two years. Kaplan–Meier survival analysis shows 64% ulcers healed at 24 weeks and 86% at one year. Ulcer recurrence rate at one and two years was 2.3% and 5.1%. Conclusions: Over one-third of superficial veins treated with foam sclerotherapy recanalised at one year and just under a quarter of superficial veins recanalised at two years. Despite this, ulcer recurrence rates were low, and recanalisation failed to predict recurrence.